Using multiple insecticidal microbial agents against diamondback moth larvae - does it increase toxicity?. Issue 2 (3rd April 2021) - Narciso, Josefina; Ormskirk, Marsha; Jones, Sandra; Rolston, Phil; Moran-Diez, Maria Eugenia; Hurst, Mark; Brookes, Jennifer; Glare, Travis
ABSTRACT: The use of microbial insect pathogens as biocontrol agents is a well-established practice, with several bacteria and fungi available in commercial products. However, lack of efficacy, persistence and restricted host ranges are limiting the widespread uptake of insect pathogens. Combining multiple agents into a single product may overcome some limitations, if they are compatible and could provide synergy. In laboratory bioassays and field applications, we examined the combined effect of two insecticidal bacteria, Yersinia entomophaga MH96 and Brevibacillus laterosporus (1951 and 1821) and the entomopathogenic fungus, Beauveria bassiana J18 against larvae of diamondback moth, Plutella xylostella . In laboratory bioassays, effects of combined bacterial agents were greater than additive at lower doses, but less than additive at higher dose. Results of the field trial showed no significant difference between the combined agents and the single treatments in most cases, although there was reduction in insect damage in combined treatments.